Design of a Research and Training Platform for Operating Portable Chainsaws Using Virtual Reality Technology - Mieszko WODZYŃSKI; Mieszko WODZYŃSKI (Projekt platformy badawczo-szkoleniowej do obsługi przenośnych pilarek łańcuchowych z zastosowaniem technologii wirtualnej rzeczywistości, 2020)
The logging industry belongs to one of the industrial processing branches with the greatest risk of accidents at work. Unfortunately, such situations often result in serious injuries and even the deaths of employees. In most cases, the casualties are people who are badly trained and inexperienced, with a short employment history. One solution to avoid these tragedies is to support workers employed in this industry with training applications. This paper presents a description of a research and training platform for operating portable chainsaws using virtual reality (VR) technology. The platform simulates phenomena occurring while working with a chainsaw, such as falling tree parts, the occurrence of chips and characteristic sound effects. The study used the HTC Vive Pro set and a dummy chainsaw with an electric module, thanks to which the application lets you control a virtual chainsaw using a real life device tracked by a system for mapping objects in space. For the purpose of this work, a series of 32 tests were conducted with 16 subjects and conclusions were drawn on the basis of test reports and surveys, in which the subjects expressed their opinions about the course of events in the platform application.
Keywords: Rzeczywistość wirtualna; Rzeczywistość wirtualna